2021
DOI: 10.3389/fnut.2021.773550
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Phenolic Compounds, Carotenoids, and Antioxidant Properties in Leaves of South African Cultivars, Peruvian 199062.1 and USA's Beauregard

Abstract: In this study, leaves of sweet potato cultivars from South Africa (“Ndou,” “Bophelo,” “Monate,” and “Blesbok”), “Beauregard,” a sweet potato cultivar from the USA, and a Peruvian cultivar “199062. 1” were analyzed using UPLC/QTOF/MS and chemometrics, with the aim of characterizing the locally developed sweet potato cultivars and comparing them with already well-known established varieties on the market. A set of 13 phenolic compounds was identified. A partial least squares discriminant analysis, a hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 27 publications
(45 reference statements)
1
14
1
6
Order By: Relevance
“…Based on the proximity of data points, the SCK and SM500 groups of the substrate-grown Chinese chives showed similar amino acid metabolisms. The PLS-DA loading plots indicated that the greater the distance between the metabolite points and the origin, the greater the contribution of the metabolite to the total variation ( 64 ) ( Figures 3C , 4C ). Among the substrate-grown Chinese chives, lysine and glutamine were positively loaded on PC2 and separated the 500 μM MeJA-treated group from other treatment groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the proximity of data points, the SCK and SM500 groups of the substrate-grown Chinese chives showed similar amino acid metabolisms. The PLS-DA loading plots indicated that the greater the distance between the metabolite points and the origin, the greater the contribution of the metabolite to the total variation ( 64 ) ( Figures 3C , 4C ). Among the substrate-grown Chinese chives, lysine and glutamine were positively loaded on PC2 and separated the 500 μM MeJA-treated group from other treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…The carotenoids in Chinese chives mainly included β-carotene. Lutein enhances the immune function and improves the antioxidant capacity of the body, protects vision, and reduces the severity of age-related macular degeneration ( 64 , 85 ). The levels of most carotenoids, such as lutein, violaxanthin, zeaxanthin, and α-carotene, were significantly higher in the substrate-grown Chinese chives treated with MeJA (500 μM) than in the SCK group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na maioria das áreas de produção de batata-doce, a folhagem é descartada após a colheita das raízes tuberosas (JACKSON et al, 2019), ou é utilizada para alimentação animal (SHUMBUSHA et al, 2017). Entretanto, existem comunidades rurais na África Subsaariana, por exemplo, que aproveitam as folhas e ramas para alimentação, como se fosse uma hortaliça folhosa (LUKUYU et al, 2014;SHUMBUSHA et al, 2017;JACKSON et al, 2019;PHAHLANE et al, 2021). Há estudos que indicam que as folhas e ramas sejam tão nutritivas quanto as raízes tuberosas e outras hortaliças folhosas devido ao alto teor de proteínas e vitaminas e ser fonte de fibras, carboidratos, minerais, polifenóis (TRUONG et al, 2007;PHAHLANE et al, 2021) e antocianinas (SHUMBUSHA et al, 2017;JACKSON et al, 2019).…”
Section: Plantas Com Valor Ornamental E Comestívelunclassified
“…Além disso, possui propriedades medicinais devido aos compostos biologicamente ativos (JACKSON et al, 2019;PHAHLANE et al, 2021). Sendo assim, variedades de batatas-doces foram desenvolvidas com a finalidade de serem consumidas como hortaliças folhosas (ISHIGURO et al, 2004;JACKSON et al, 2019).…”
Section: Plantas Com Valor Ornamental E Comestívelunclassified